Total phenolic contents and free-radical scavenging activities from methanolic extracts of Nauclea subdita (Korth) Steud. heartwood - Jamaluddin, Fatin Ruzanna; Wahab, Razak; Mohd Daud, Jamaluddin; Rahman, Shafiqur (AENSI, 2012)
Investigation on the total phenolic content (TPC) and free-radical scavenging activity of Nauclea subdita (Korth) Steud. were carried out. Information on these activities might reflect the potency of the plant extract as an antioxidant. Young and matured trees of N. subdita were harvested and cut into three heartwood parts (top, middle and bottom) and grounded into powdered forms. Soxhlet extraction of the heartwood samples using polar (methanol) and non-polar (hexane) solvents, and phytochemical screening tests were carried out. The total phenolic contents of the methanolic crude extracts from heartwood parts were determined by colorimetry at 760 nm using Folin-Ciocalteau’s reagent, and gallic acid was used as standard. The methanolic extracts were also checked for primary antioxidant activities using an in vitro method, measured by free-radical scavenging activity of 2, 2’-diphenyl-1- picrylhydrazyl (DPPH) radical. The absorbances were measured at 517 nm by UV/VIS spectrophotometer and compared with standards Trolox and butylated hydroxyanisole (BHA). The results from this study suggest that N. subdita heartwood extract may serve as a potential source of natural antioxidant for future development in food and nutraceutical applications.